Nonlinear QED in an ultrastrong rotating electric field: Signatures of the momentum-dependent effective mass - E. Raicher; K. Z. Hatsagortsyan (Physical Review Research, 2020)
The electron effective mass in a rotating electric field (REF) and its signatures in the nonlinear Breit-Wheeler and nonlinear Compton processes are investigated, recognizing this field as a model for the antinodes of counterpropagating laser beams. In contrast to the case of a plane-wave laser field, the effective mass in REF depends on the electron momentum absolute value as well as on its direction with respect to the field plane. These features of the effective mass are observable in the threshold for pair production by a γ photon, and in the harmonics structure appearing in the radiation spectrum of an electron. It can be tested varying the photon propagation direction in the first case, and the electron energy in the second case. Thus, we demonstrate the possibility of a nontrivial dispersion relation for an electron in strong laser fields, analogous to that in condensed-matter systems, which leaves its imprints in high-energy scattering.